2019
DOI: 10.35940/ijitee.a6119.119119
|View full text |Cite
|
Sign up to set email alerts
|

Pitch Pattern Analysis in Speech of Children with Autism Spectrum Disorder

Abstract: Autism Spectrum Disorder (ASD) is a multifaceted neurodevelopmental condition. Atypical communication mostly occurs in tandem with ASD. We compared voice pitch of 16 Marathi children and adolescents with ASD of age of 7 to 18 with 27 Typically Developing (TD). Speech samples have been recorded and stored in .wav format with sampling frequency of 48000 Hz. For analysis we used PRAAT, a program for speech analysis, manipulation and synthesis. We divided the ASD and TD group into total 4 groups on basis of age an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…Sheinkopf et al, investigating the acoustic characteristics of infants’ crying sound reported two mean pitch values for pain-related and non-pain-related cries. Furthermore, 11 studies 13 , 15 , 18 , 29 , 38 , 45 , 49 , 58 60 , 63 found no significant difference (p > 0.05) between groups. By analyzing adult male participants (age > 13), Nayak et al found a higher mean pitch value for ASD than TD group, while for younger male participants (age < 13), the mean pitch value was not different between groups 38 .…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Sheinkopf et al, investigating the acoustic characteristics of infants’ crying sound reported two mean pitch values for pain-related and non-pain-related cries. Furthermore, 11 studies 13 , 15 , 18 , 29 , 38 , 45 , 49 , 58 60 , 63 found no significant difference (p > 0.05) between groups. By analyzing adult male participants (age > 13), Nayak et al found a higher mean pitch value for ASD than TD group, while for younger male participants (age < 13), the mean pitch value was not different between groups 38 .…”
Section: Resultsmentioning
confidence: 90%
“…The results of these studies were completely inconsistent. Two studies 14 , 62 reported lower mean pitch value for vocal productions of people with ASD, while ten other studies 10 , 17 , 22 , 38 , 39 , 47 , 61 , 62 , 64 , 65 found higher mean pitch value for ASD individuals. Sheinkopf et al, investigating the acoustic characteristics of infants’ crying sound reported two mean pitch values for pain-related and non-pain-related cries.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…период обучения игре на саксофоне является самым трудным и наиболее важным для успешного овладения искусством игры на саксофоне ([3 , [2], [4]).…”
unclassified